How are “Atypical” Sulfite Dehydrogenases Linked to Cell Metabolism? Interactions between the SorT Sulfite Dehydrogenase and Small Redox Proteins - Low, Louie; Kilmartin, James R.; Bernhardt, Paul V.; Kappler, Ulrike (Frontiers in Microbiology, 2011)
Sulfite dehydrogenases are enzymes that catalyze the oxidation of the toxic and mutagenic compound sulfite to sulfate, thereby protecting cells from adverse effects associated with sulfite exposure. While some bacterial sulfite dehydrogenases that have been characterized to date are able to use cytochrome c as an electron acceptor, the majority of these enzymes prefer ferricyanide as an electron acceptor and have therefore been termed ‘atypical’ sulfite dehydrogenases. Identifying the natural electron acceptor of these enzymes, however, is crucial for understanding how the ‘atypical’ sulfite dehydrogenases are integrated into cell metabolism. The SorT sulfite dehydrogenase from Sinorhizobium meliloti is a representative of this enzyme type and we have investigated the interactions of SorT with two small redox proteins, a cytochrome c and a Cu containing pseudoazurin, that are encoded in the same operon and are co-transcribed with the sorT gene. Both potential acceptor proteins have been purified and characterized in terms of their biochemical and electrochemical properties, and interactions and enzymatic studies with both the purified SorT sulfite dehydrogenase and components of the respiratory chain have been carried out. We were able to show for the first time that an ‘atypical’ sulfite dehydrogenase can couple efficiently to a cytochrome c isolated from the same organism despite being unable to efficiently reduce horse heart cytochrome c, however, at present the role of the pseudoazurin in SorT electron transfer is unclear, but it is possible that it acts as an intermediate electron shuttle between. The SorT system appears to couple directly to the respiratory chain, most likely to a cytochrome oxidase.